Etiology of Clinical Community-Acquired Pneumonia in Swedish Children Aged 1-59 Months with High Pneumococcal Vaccine Coverage-The TREND Study - Eklundh Annika; Rhedin Samuel; Ryd-Rinder Malin; Andersson Maria; Gantelius Jesper; Gaudenzi Giulia; Lindh Magnus; Peltola Ville; Waris Matti; Nauclér Pontus; Mårtensson Andreas; Alfvén Tobias (MDPI, 2022)
(1) Immunization with pneumococcal conjugate vaccines has decreased the burden of community-acquired pneumonia (CAP) in children and likely led to a shift in CAP etiology. (2) The Trial of Respiratory infections in children for ENhanced Diagnostics (TREND) enrolled children 1-59 months with clinical CAP according to the World Health Organization (WHO) criteria at Sachs' Children and Youth Hospital, Stockholm, Sweden. Children with rhonchi and indrawing underwent "bronchodilator challenge". C-reactive protein and nasopharyngeal PCR detecting 20 respiratory pathogens, were collected from all children. Etiology was defined according to an a priori defined algorithm based on microbiological, biochemical, and radiological findings. (3) Of 327 enrolled children, 107 (32%) required hospitalization; 91 (28%) received antibiotic treatment; 77 (24%) had a chest X-ray performed; and 60 (18%) responded to bronchodilator challenge. 243 (74%) episodes were classified as viral, 11 (3%) as mixed viral-bacterial, five (2%) as bacterial, two (0.6%) as atypical bacterial and 66 (20%) as undetermined etiology. After exclusion of children responding to bronchodilator challenge, the proportion of bacterial and mixed viral-bacterial etiology was 1% and 4%, respectively. (4) The novel TREND etiology algorithm classified the majority of clinical CAP episodes as of viral etiology, whereas bacterial etiology was uncommon. Defining CAP in children <5 years is challenging, and the WHO definition of clinical CAP is not suitable for use in children immunized with pneumococcal conjugate vaccines.